Profitabilitas dan Return Saham: Peran Moderasi Arus Kas Operasi dan Ukuran Perusahaan - Murni Prasetyaningrum (Jurnal Ekonomi dan Bisnis, 2014)
This study aims to determine the effect of profitability on stock returns with operating cash flow and firm sizeas a moderating variable of companies listed on the Indonesia Stock Exchangein 2006-2008. The population in this study is all companies listed on the Indonesia Stock Exchange. Sample is taken by using purposive sampling method. The hypothesisis tested using regression with variable moderation. Results of this study show that profitability has a positive effecton stock returns, operating cash flow does not significantly moderate the relationship between profitability and stock returns, firm size does not moderate the relationship between profitability and stock returns.